The Effect of Blanching Time on The Healthy Salt Characteristics of Seablite (Suaeda Maritima) - Dewi Oktaviani; Iffan Maflahah; Supriyanto (Agroindustrial Technology Journal, 2023)
Sea salt has long been applied as food complement, but its use as ingredient receives serious health concern in last decade. Healthier salt containing NaCl no more than 60% is accepted as the promising option replacing the conventional one. The sealible plant (Suaeda maritima) can be procesesed into healthy salt. The plant grows well in muddy swamps of coastal areas, which make it have high salinity. The aim of this research was to determine the characteristics of healthy salt prepared from furrow plants using different levels of blanching time and activated charcoal. This research design followed a non-factorial completely randomized design (CRD) with different blanching time (no blanching, 3 min, 6 min, and 9 min) and the addition of activated charcoal (1.5%). The salt quality was checked for yield, water content, ash content, NaCl content, mineral content, salinity, vitamin A and phytochemicals. The results of the research showed that the furrow plant salt showed significant differences of salt characteristics in terms of yield, water content, ash content, NaCl content, minerals, salinity and vitamin A.